Исходењето на Светиот Дух во теологијата на свети Атанасиј Велики и улогата на Духот во спасението на човекот - Nedeski, Viktor (Православен богословски факултет „Св. Климент Охридски“ Скопје, 2018)
There are real difficulties in establishing the doctrine of the proceeding of the Holly Spirit at this early stage of Pneumatology, and subsequently in the teaching of St. Athanasius the Great. What remains is the fact that the purpose of St. Athanasius in the Epistles to Serapion of Thmuis was not in any way the question of the proceeding, but the proving of the divinity of the Holy Spirit, based on biblical and traditional principles. The main reason for the divergence of views of modern Eastern and Western scholars on the question of the proceeding of the Holy Spirit in these epistles is not the doctrine of St. Athanasius in itself, but the later theological principles under which scholars are guided, and which would have evolved differently in the eastern and western theological tradition. For St. Athanasius, Christ would be lost as an isolated, inexplicable, historical enigma without the testimony of the Spirit in humanity, and this testimony is greater than any philosophical or dogmatic conception. Thus, it is evident that the meaning of participation in the Holy Trinity is central to the understanding of the entire theological thought of St. Athanasius the Great. Man is able to receive eternal communion with God, not only by simply identifying himself with Christ and His teaching, but by participating in Him. It is made possible by the action of the Holy Spirit.